Qingpeng Ointment Ameliorates Inflammatory Responses and Dysregulation of Itch-Related Molecules for Its Antipruritic Effects in Experimental Allergic Contact Dermatitis - Gong, Xuan; Xiong, Hui; Liu, Sisi; Liu, Yutong; Yin, Liang; Tu, Chuyue; Wang, Hua; Zhao, Zhongqiu; Chen, Weiwu; Mei, Zhinan (Frontiers in Pharmacology, 2019)
The pathogenesis of itchy skin diseases including allergic contact dermatitis (ACD) is complicated and the treatment of chronic itch is a worldwide problem. One traditional Tibetan medicine, Qingpeng ointment (QP), has been used in treatment of ACD in China for years. In this study we used HPLC and LC/MS analysis, combined with a BATMAN-TCM platform, for detailed HPLC fingerprint analysis and network pharmacology of QP, and investigated the anti-inflammatory and antipruritic activities of QP on ACD induced by squaric acid dibutylester (SADBE) in mice. The BATMAN-TCM analysis provided information of effector molecules of the main ingredients of QP, and possible chronic dermatitis-associated molecules and cell signaling pathways by QP. In ACD mice, QP treatment suppressed the scratching behavior induced by SADBE in a dose-dependent manner and inhibited the production of Th1/2 cytokines in serum and spleen. Also, QP treatment reversed the upregulation of mRNAs levels of itch-related genes in the skin (TRPV4, TSLP, GRP and MrgprA3) and DRGs (TRPV1, TRPA1, GRP, and MrgprA3). Furthermore, QP suppressed the phosphorylation of Erk and p38 in the skin. In all, our work indicated that QP can significantly attenuate the pathological alterations of Th1/2 cytokines and itch-related mediators, and inhibit the phosphorylation of MAPKs to treat the chronic itch.